Characteristic of Generative Growth of Asystasia gangetica at Various Dosages and Time of Decomposition of Organic Goat Manure Fertilizer - Duarsa, Magna Anuraga Putra; Suryani, Ni Nyoman; Suarna, I Wayan (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 12 No 1 (2022): Pastura Vol. 12 No. 1 Tahun 2022DO - 10.24843/Pastura.2022.v12.i01.p12, 2022)
The objective of this experiment was to study the generative growth of Asystasia gangetica at various dosages and time of decomposition of goat manure. Completely randomized design was applied in this experiment, with two factors. The first factor was time of decomposition, with consisted of three levels, namely 4 weeks of decomposition, 2 weeks and without decomposition. The second factor was goat manure fertilizer with four dosages, namely 0 ton ha -1 , 10 ton ha -1 , 20 ton ha -1 , and 30 ton ha -1 . Every treatment combination was repeated four times, therefore total 48 pots were used. First time flowering, total seed production, seed weight per 100 seeds, total seed petals, seed dimension (length, width and thickness) were measured as variables. The results of this experiment showed that there were no interactions between factors at all variabels. Aplication 10 ton ha -1 of goat manure, significantly lengthen flowering for the first time of Asystasia , however time of decomposition gave no effect to this variable. Increasing the level of goat manure fertilizer to 10 ton ha -1 also significantly increase seed production per pot, however significantly decreased seed weight per 100 seeds. Seed dimension (length, width and thickness) were not significantly affected by both dosages of goat manure fertilizer and time of decomposition. It can be concluded that application of 10 ton ha -1 of goat manure lengthen flowering for the first time, increase seed production per pot and decrease seed weight per 100 seeds of Asystasia .   Key words: Asystasia gangetica, decomposition, goat manure fertilizer, generative growth